Implications of Migrationon Income and Welfare of Nationals - Ueda, Kenichi (Washington, D.C. : International Monetary Fund, 2002)
As labor has become more mobile in today's world, it is important to understand the income and welfare of nationals regardless of their residence. This paper develops two key concepts, gross migration-corrected product (GMP) and welfare cost of migration, and calculates them using New Zealand data. Growth performance measured by New Zealanders' income has been clearly better than suggested by the GDP. The welfare cost associated with a marginal change in the tax rate appears quite high.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet